The influence of organizational justice and perceptual support of organizations on Organizational Citizenship Behavior (OCB) teachers at SMA Negeri East Jakarta Area 1: Indonesia - Dian Sari Mulyana; Matin Matin; Siti Rochana (Program Studi Manajemen Pendidikan, 2020)
Abstract The purpose of research: knowing deeply about the influence of organizational justice towards the perception of organizational support, organizational support for OCB Justice organization affects the OCB site research place of East Jakarta Area 1. Research conducted for 12 months from July 2018 until June 2019 the method used is a survey with a quantitative approach. The results showed that justice organizations were positively related to Organizational Citizenship Behavior (OCB). That is, the better and conducive justice of the organization then the increasing behavior organizational citizenship behavior of senior high school teachers in East Jakarta Region 1 perception of organizational support (POS) berhubungan positif dengan organizational citizenship behavior. That is, the better the perception of organizational support, the higher organizational citizenship behavior of SMA Negeri teachers in East Jakarta Region 1. Fairness of organizational and organizational support perception jointly relates positively to organizational citizenship behavior. That is, the better and conducive justice of the Organization and the more positive the perception of organizational support together, the stronger the organizational citizenship behavior of senior high school teachers in East Jakarta region. 1